Ethnobotany of India-A book review - Malik, Zubair A.; singh, Sushma (Ethnobotany Research and Applications, 2026)
Ethnobotany of India. Volume I (2025): Edited by: Emdad Hossain, Anjali Jaiswal, Bidhan Chandra Roy and Sanjeet Kumar; APRF Publishers, Odisha, India, pp x +126; ISBN: 978-81-984754-7-3. Price: ₹1250 Ethnobotany of India. Volume II (2025): Edited by: Bidhan Chandra Roy, Emdad Hossain and Sanjeet Kumar; APRF Publishers, Odisha, India, pp x +130; ISBN: 978-81-985655-6-3. Price: ₹1450 Ethnobotany of India (Volumes I and II), edited by Emdad Hossain, Anjali Jaiswal, Bidhan Chandra Roy, and Sanjeet Kumar, represents a coordinated effort by the Ambika Prasad Research Foundation (APRF) to document India’s diverse ethnobotanical knowledge. Drawing on contributions from researchers working across varied ecological regions and cultural settings, the two volumes aim to present a contemporary picture of ethnobotanical research in India while underscoring the urgency of recording indigenous plant knowledge that is increasingly threatened by socio-economic change, habitat loss, and cultural transitions. Given India’s exceptional biological and cultural diversity, ethnobotanical documentation remains both complex and essential. In this context, the present work seeks to capture traditional plant-based knowledge across regions and communities, while also exploring its relevance to healthcare, conservation, and applied research.